2022
DOI: 10.54938/ijemdm.2022.01.3.122
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional MHD Viscous Flow Under the Influence of Thermal Radiation and Viscous Dissipation

Abstract: The present study elucidates the results on the mathematical modeling and numerical study for the viscous flow demeanor past over the plane horizontal surface stretched nonlinearly in two sideways. Furthermore, a comprehensive analysis on the effects of magnetic field, thermal radiation and viscous dissipation are considered and observed. Cartesian coordinate system is employed for modelling the flow equations. In this research water act as a traditional thermal fluid. Three distinct nanoparticles namely Gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A comprehensive study found that the most prevalent methods for enhanced heat transmission in nanofluids include Brownian motion-induced convection and consecutive transmission via propagating nanoparticle pathways. Numerous scholars [12][13][14][15][16][17] have examined Brownian motion and thermophoresis consequences in great depth. With heat augmentation as their ultimate aim, their research examined a wide variety of technical setups.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study found that the most prevalent methods for enhanced heat transmission in nanofluids include Brownian motion-induced convection and consecutive transmission via propagating nanoparticle pathways. Numerous scholars [12][13][14][15][16][17] have examined Brownian motion and thermophoresis consequences in great depth. With heat augmentation as their ultimate aim, their research examined a wide variety of technical setups.…”
Section: Introductionmentioning
confidence: 99%
“…Alaidrous [12] explored the complexities of three‐dimensional electromagnetic radiative non‐Newtonian nanofluid flow within porous materials, considering Joule heating and higher‐order reactions. Akbar and Sohail [13] investigated three‐dimensional magnetohydrodynamic (MHD) viscous flow influenced by thermal radiation and viscous dissipation. Their research delves into the effects of magnetic fields and thermal processes on fluid dynamics, relevant to applications in energy and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, analyzing strong magnetic field with low density is very important, which is distinguished as the Hall current. It has a wide rangr of applications in engineering areas like power generators and warming elements 21 , 22 . As well, Joule heating is generated while electricity force transmits to temperature via resistance 23 25 .…”
Section: Introductionmentioning
confidence: 99%